F08 The autoimmune profile of Huntington's disease patients: a pilot study. (29th August 2012) - Goehler, H; Kowald, A; Turewicz, M; Stephan, C; Meyer, HE; Lueking, A; Schottstedt, V; Woitalla, D; Hoffmann, R; Gold, R; Saft, C
Abstract : Huntington's disease (HD) is a progressive neurodegenerative disorder, which is caused by expansion of a polyglutamine tract in the first exon of the huntingtin gene. Genetic testing allows the unambiguous diagnose of HD and the identification of individuals carrying the gene defect before onset of clinical symptoms. However, molecular markers that are suited to predict disease onset, monitor disease progression and asses the response to therapy are still not available. To identify HD-specific molecular markers we performed a comparative analysis of the autoimmune profile of symptomatic patients, presymptomatic gene carriers and a representative control cohort. Serum samples were tested for antigen/autoantibody interactions using a sequential arrangement of protein macroarrays and microarrays. The macroarrays contained E coli clones expressing approximately 10 000 human proteins and were used to characterise the autoimmune profile of 20 HD patients. Hereby, 273 human proteins were selected to generate a HD-specific protein microarray. Serum samples of 100 HD patients, 29 presymptomatic gene carriers and 100 healthy individuals were analysed using the HD-specific microarray. Thereby, several autoantigens were detected that represent putative molecular markers for HD. Further validation experiments are necessary to confirm the relevance of the identified molecular markers. The presence of HD-specific autoantibodies in serum samples supports the idea that progression of HD is associated with alterations of the immune system.